Incentive provision as a moderating variable and organizational commitment as a mediating variable in improving employee performance - Wiedya Riski Purnamasari; Fauji Sanusi; Liza Mumtazah Damarwulan (Jurnal Mantik, 2023)
This study aimed to test and analyze the role of incentives as a moderating variable and organizational commitment as a mediating variable in improving employee performance at Kencana Hospital, Serang City. The population in this study were all employees of Kencana Hospital Serang City. In this study, a saturated/total sample was used for sampling, meaning all employees were sampled, totaling 243 respondents. The data analysis technique with SEM PLS version 4.0 has been used to analyze the data. Two hundred forty-three questionnaires have been collected with the interval method one disagree- 10 strongly agree. The results showed that training effectiveness does not have a significant effect on employee performance, preventive work discipline has a significant effect on employee performance, training effectiveness has a significant effect on organizational commitment, preventive work discipline has a significant effect on organizational commitment, organizational commitment has a significant effect on employee performance, providing incentives can moderate the effect of organizational commitment on employee performance. Providing appropriate incentives can be a driver and give the effect of organizational commitment to improving employee performance. The first mediation can be characterized as complete mediation, while the second mediation can be characterized as partial mediation. This research is expected to make a theoretical contribution to the literature in this context, among others, in human resource management.